2021
DOI: 10.1182/blood.2021012663
|View full text |Cite
|
Sign up to set email alerts
|

Murine bone marrow mesenchymal stromal cells have reduced hematopoietic maintenance ability in sickle cell disease

Abstract: Sickle Cell Disease (SCD) is characterized by hemolytic anemia, which can trigger oxidative stress, inflammation, and tissue injury that contributes to disease complications. Bone marrow mesenchymal stromal cells (MSCs) tightly regulate hematopoietic stem cell (HSC) homeostasis in health and disease but their functionality in SCD remains unclear. We identified for the first time murine SCD MSCs to have altered gene signatures, reduced stem cell properties, and increased oxidative stress, due in part to hemolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Alterations in SCD HSCs were reported by Tang et al, who showed a decrease in HSC frequency, increased DNA damage, and an accumulation of ROS in HSCs from SCD mice, associated with the reduced hematopoietic supportive ability of MSCs [ 115 ].…”
Section: The Hsc Niche In Bthal and Scdmentioning
confidence: 99%
See 4 more Smart Citations
“…Alterations in SCD HSCs were reported by Tang et al, who showed a decrease in HSC frequency, increased DNA damage, and an accumulation of ROS in HSCs from SCD mice, associated with the reduced hematopoietic supportive ability of MSCs [ 115 ].…”
Section: The Hsc Niche In Bthal and Scdmentioning
confidence: 99%
“…The status of HSCs and BM niche, indeed, should be considered in the context of allogeneic HSCT to ensure a sustained engraftment of donor cells and especially in recent autologous gene therapy settings, to develop optimized protocols for increasing the efficacy and safety of ex-vivo genetic manipulation [ 44 ]. The reduced number of HSCs available for collection and the impaired engraftment potential of HSCs in BThal and SCD mouse models [ 114 , 115 ] highlighted the need for a better characterization of the primitive HSC compartment and BM niche features to develop targeting strategies for improving the outcome of allogeneic and autologous HSCT.…”
Section: The Hsc Niche In Bthal and Scdmentioning
confidence: 99%
See 3 more Smart Citations